Pelatihan Konten Kreatif Canva Sebagai Upaya Pemanfaatan Media Digital Untuk Masyarakat Desa Tengaran - Isnaini Lathifah Fajriatun; Muhammad Nafiis Ilhami; Ifa Ditta Arimindani; Ely Armawati; Norma Eralita (Universitas Negeri Semarang, 2025)
Rural communities generally experience problems in creating creative content, especially graphics, such as posters, pamphlets, and others. In terms of design and making attractive content, it can be done by using free applications that offer a variety of templates that can be used to create customized designs based on needs. One of these applications is Canva. This activity program is carried out in the form of empowerment for PKK mothers and youth organizations in Tengaran Village, related to Canva's creative content as an effort to utilize digital media. This program aims to serve as an introduction in an effort to utilize the Canva application for the community in Tengaran Village. This activity was held to increase community interest in creating creative content easily through the use of digital media. Creative content training using the Canva application aimed at PKK mothers and youth organizations has a positive impact on improving digital skills